2020
DOI: 10.3390/su13010075
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Factors Affecting SME Performance: The Mediating Role of Social Media Adoption

Abstract: Small and medium enterprises (SMEs) have become a vibrant and dynamic sector of the world economy. Information technology plays a vital role in improving the productivity and competitiveness of SMEs. The dynamic business environment has brought fierce competition among SMEs and, therefore, requires the owners to interact with internal and external members actively. Hence, this study aims to investigate the impact of technology, organization, and environment as important factors in the performance of small and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
111
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(181 citation statements)
references
References 98 publications
18
111
0
4
Order By: Relevance
“…This study used the Kaiser–Meyer–Olkin (KMO) test to measure the sampling adequacy and ensure data suitability. The KMO test result was 0.874, which is greater than an acceptable threshold of 0.50 (Ali Qalati et al, 2021 ; Shrestha, 2021 ), and hence considered suitable for explanatory factor analysis. Moreover, Bartlett's test results demonstrated a significance level of 0.001, which is considered good as it is below the accepted threshold of 0.05.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…This study used the Kaiser–Meyer–Olkin (KMO) test to measure the sampling adequacy and ensure data suitability. The KMO test result was 0.874, which is greater than an acceptable threshold of 0.50 (Ali Qalati et al, 2021 ; Shrestha, 2021 ), and hence considered suitable for explanatory factor analysis. Moreover, Bartlett's test results demonstrated a significance level of 0.001, which is considered good as it is below the accepted threshold of 0.05.…”
Section: Resultsmentioning
confidence: 89%
“…There are several reasons for CMB: (1) it mainly occurs due to response “tendencies that raters can apply uniformity across the measures;” and (2) it also occurs due to similarities in the wording and structure of the survey items that produce similar results (Jordan and Troth, 2019 ). Harman's single factor test and a full collinearity approach were employed to ensure that the data was free from CMB (Tehseen et al, 2017 ; Jordan and Troth, 2019 ; Ali Qalati et al, 2021 ). Harman's single factor test showed a single factor explained only 22.8% of the total variance, which is far below the 50.0% acceptable threshold (Podsakoff et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, [20] proposed SM as a potential mechanism that indirectly affects resources and performance, while [10] suggested that the direct EO-firm-performance link is be mediated and moderated by different constructs. Recently, [69,79,85] evidenced the mediating role of SM adoption in SMEs' context in developing countries. Thus, we argue that EO enhances SME performance indirectly by affecting SM adoption:…”
Section: Mediating Role Of Sm Adoptionmentioning
confidence: 99%
“…Information technology plays a vital role in improving the productivity and competitiveness of SMEs. The dynamic business environment has brought fierce competition among SMEs and, therefore, requires the owners to actively interact with internal and external members [142,143].…”
Section: Determinants Of Human Resource Capacity and Productivity Of Smesmentioning
confidence: 99%